1983
DOI: 10.1113/jphysiol.1983.sp014819
|View full text |Cite
|
Sign up to set email alerts
|

Paralysis of frog skeletal muscle fibres by the calcium antagonist D‐600.

Abstract: SUMMARY1. The Ca2+ channel blocker D-600 (methoxyverapamil) paralyses single muscle fibres of the frog: fibres exposed to the drug at 7 0C give a single K+ contracture after which they are paralysed, unable to contract in response to electrical stimulation or further applications of K+.2. Paralyzed fibres contract in response to caffeine and have normal resting potentials and action potentials.3. Fibres treated with D-600 at 22 0C are not paralysed. Paralysed fibres warmed to 22 0C recover contractile properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
60
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 35 publications
12
60
0
Order By: Relevance
“…Experiments in 2 H2O were made after waiting for the equilibration time (ϳ20 min) to allow a complete exchange of 2 H2O for water in the fiber. The responses in D600 were obtained in normal Ringer during the force recovery from the paralysis induced by exposing the fiber, loaded with D600, to high-potassium solution, as described previously (10,19). We also evaluated the effects of nitrate Ringer (92 mM NaCl substituted by NaNO 3) on fibers perfused with 6.25 M Dantrolene to verify the possibility of reversing the Dantrolene effect on static stiffness with a Ca 2ϩ release potentiator (21,24).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in 2 H2O were made after waiting for the equilibration time (ϳ20 min) to allow a complete exchange of 2 H2O for water in the fiber. The responses in D600 were obtained in normal Ringer during the force recovery from the paralysis induced by exposing the fiber, loaded with D600, to high-potassium solution, as described previously (10,19). We also evaluated the effects of nitrate Ringer (92 mM NaCl substituted by NaNO 3) on fibers perfused with 6.25 M Dantrolene to verify the possibility of reversing the Dantrolene effect on static stiffness with a Ca 2ϩ release potentiator (21,24).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown previously that the presence of D600 greatly prolongs inactivation of the voltage sensors, but that it has little effect on the sensors when they are in their resting state (Eisenberg, McCarthy & Milton, 1983;Berwe, Gottschalk & Liittgau, 1987;Feldmeyer, Melzer & Pohl, 1990;Lamb & Stephenson, 1990 b). In all three 518 EFFECT OF Mg2+ ON Ca2+ RELEASE IN MUSCLE fibres examined, a single depolarization in 10 mM-Mg2+ and 20 IaM-D600 completely abolished the response to a subsequent depolarization in 1 mM-Mg2+ (e.g.…”
Section: D600 Paralysis Upon Depolarization In 10 Mm-mg2+mentioning
confidence: 99%
“…The effect of dantrolene could be compensated by a higher caffeine concentration, whereas the action of ryanodine was irreversible. The Ca antagonist D-600, which is claimed to interfer with excitation-contraction coupling in skeletal muscle (Eisenberg, McCarthy & Milton, 1983), did not affect oscillations (30 ,sM-D-600). Kumbaraci & Nastuk (1982) showed that during oscillations a low-molecular-weight substance (mol.…”
Section: Pmentioning
confidence: 99%